Teacher Motivation and Performance: The Case of Some Selected Early Childhood Care and Education Centres in the Cape Coast Metropolis of Ghana - Odoom, Daniel; Opoku, Ernest; Ntiakoh-Ayipah, Daniel (International Journal of Innovative Research and Development, 2016)
This paper examined the level of motivation and performance among Early Childhood Care and Education (ECCE) teachers within the Cape Coast Metropolis. Using a descriptive research design, 60 respondents were selected for the study through purposive and simple random sampling techniques. Questionnaires and interview guide were used in obtaining the relevant inputs for the study. It was established that most ECCE teachers in the Cape Coast Metropolis decided to work at the centers in order to secure job and to get opportunities for career development. There was a positive correlation between ECCE teachers’ motivational factors and their level of performance. While promotion was perceived as the number one motivator mostly available at the centers, remuneration and incentives was seen as the least available motivator. The study found that wage/salary provided to teachers at the ECCE centers had the greatest relative influence on ECCE teachers’ performance, with good leadership style as the least determinant of teachers’ job performance. It is recommended that the ECCE centers in collaboration with the District Assembly should provide attractive incentives in order to motivate teachers to give off their best performance. The paper also recommends that effective ECCE programs should be gleaned from well-coordinated efforts of different partners including school managers, parents, communities, local and national governments as well as the civil society.
Research Article
Keywords: Teacher Motivation, Performance, Early Childhood Care, Education Centres, Cape Coast Metropolis, Ghana